New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper presents an empirical comparison of New Zealand's growth performance with that of Australia during the post-reform period. The paper shows that most of the divergence in income per capita between the two countries has been the result of lower accumulation of capital per hour worked, and to a lesser extent, lower efficiency in utilizing resources in New Zealand. The paper also examines how migration has affected the income and welfare of New Zealand nationals.